Identification of aflatoxins in milk and dairy products: Literature review (Research, Society and Development, 2021)
Aflatoxins are toxic metabolites of fungi of the Aspergillus genus that can be commonly found in animal and vegetable products. The objective of this study was to investigate the presence of aflatoxins in milk and its derivatives based on the consultation of works published in Brazil through the Scientific Electronic Library Online, Pubmed and Google Scholar databases. For this, sixteen papers published between 1989 and 2018 were chosen, where thirteen evaluated milk in different forms of treatment and three evaluated cheese. Of the thirteen studies on the detection of aflatoxins in milk, five showed a concentration above the limit established by the Brazilian legislation for aflatoxins in milk, being 0.010 to 0.645µg/L, 0.075 to 1.280 µg/L, 1.68 µg/L, 0 .04 to 1.05 µg/L and 0.04 to 4.64 µg/L. Of the three studies that evaluated cheese, all verified the presence of aflatoxins, but only one study identified a metabolite concentration above the maximum tolerated limit, resulting in a value between 2.7 and 6.6 µg/kg. The methodology used to detect the fungal toxin varied between the HPLC, CCD, CLUE and ELISA techniques. The presence of aflatoxins in dairy products demonstrates the importance of monitoring these products, as well as greater attention to food intended for farm animals, which is a source of indirect contamination for humans, which can impact health by chronic consumption . Therefore, the need for constant monitoring of aflatoxins in products of animal origin becomes evident, considering the natural occurrence and high toxicity of aflatoxins for human and animal health.